Diagonally implicit hybrid method for solving special second order ordinary differential equations - Samat, Faieza; Suleiman, Mohamed (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
This paper describes the derivation of a fifth-order diagonally implicit hybrid method. The method is zero dissipative and has phase-lag of order six. The method is compared with the existing hybrid method and the numerical comparisons carried out show that the new method improves the accuracy of the existing method for solving several special second order ordinary differential equations.